Core agricultural science literature project in USA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The Mann Library of Cornell University's College of Agriculture and Life Sciences has received a grant to identify the core literature of the agricultural sciences. The increased spread of information technology in the Third World and the...